Mycobacterium tuberculosis enoyl-acyl carrier protein reductase inhibitors as potential antituberculotics: development in the past decade. (August 2015) - Holas, Ondrej; Ondrejcek, Pavel; Dolezal, Martin
Abstract Mycobacterial enoyl-ACP-reductase, an enzyme contributing in mycolic acids biosynthesis, has been established as promising target of novel antimycobacterial drugs. The development of inhibitors active without previous activation by catalase/peroxidase system (e.g. isoniazid), seems to be rational approach. Catalase/peroxidase system is frequently responsible for resistance. We hereby present a review of direct mycobacterial enoyl-acyl carrier protein reductase inhibitors development in past decade. A special attention was paid to mechanism of inhibition, which shows relatively conserved interactions of inhibitors with Tyr 158 and cofactor. Hence, future developments of more effective antitubercular drugs should consider structural demands for potent direct mycobacterial enoyl reductase inhibitors.